2001
DOI: 10.1097/00002480-200111000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of an Air Filter at the Drainage Site in a Closed Circuit with a Centrifugal Blood Pump: An In Vitro Study

Abstract: In a closed circuit with a centrifugal blood pump, one of the serious obstacles to clinical application is sucking of air bubbles into the drainage circuit. The goal of this study was to investigate the efficiency of an air filter at the drainage site. We used whole bovine blood and the experimental circuit consisted of a drainage circuit, two air filters, a centrifugal blood pump, a membrane oxygenator, a return circuit, and a reservoir. Air was injected into the drainage circuit with a roller pump, and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…To minimize microbubble entry to the circulation, a filter is attached to the tube that returns the blood to the patient. This solution is incomplete, as bubbles have been detected in the cerebral circulation (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize microbubble entry to the circulation, a filter is attached to the tube that returns the blood to the patient. This solution is incomplete, as bubbles have been detected in the cerebral circulation (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns over patient safety by using a MECC system without a safety feature to remove venous air have been raised [ 57,58 ] . Under such circumstances, a potential risk for continuous microair embolisation exists during perfusion.…”
Section: Venous Bubble Trapmentioning
confidence: 99%
“…Various in vitro studies have shown that the air handling capability of closed-loop systems is low compared to conventional CPB systems (3,14,20). In contrast, two recent studies reported a lower embolic load in patients perfused with a MECC system as compared to a conventional CPB system during CABG (10,11).…”
Section: Air Removal Efficiency Of a Venous Bubble Trap 1095mentioning
confidence: 99%
“…Others have also raised their concerns over patient safety by using a miniaturized extracorporeal circulation system, without a safety feature to remove venous air (13,14).…”
mentioning
confidence: 99%